Spatial memory impairment by hippocampal oxidative stress in male Long-Evans rats-Can it be prevented and/or alleviated by climbing exercise? - Ali, Taskina; Amin, Rokhsana Binte; Basak, Puspita; Akter, Fhamida; Islam, Md Saiful; Islam, Kazi Rafiqul (Journal of Bangladesh Society of Physiologist, 2025)
Background: Drug treatment for Spatial memory impairment has a wide range of adverse effects. Objective: To assess the effects of climbing exercise (CE)on spatial memory performance and hippocampal oxidative stress in colchicine induced memory impaired rats. Methods: Thirty male Long-Evans rats (8±2weeks; 225±75 gm)were grouped (6 rats/group)into normal control, sham control, colchicine control, pre colchicine CE and post colchicine CE. In CE, each rat performed 08 to 12 climbs/hour in a climbing tool for consecutive 28 days. Then, reference memory (RM) [Mean escape latency (EL) in acquisition phase, average EL of 5th and 6thacquisition days; number of target crossing (TC) and time spent in target (TT) in probe trial] and working memory (WM) [Mean EL and savings in training and test phase] were assessed by Morris water maze (MWM) test. Then, after sacrifice, hippocampal malondialdehyde (MDA) and glutathione peroxidase (GPx) were estimated. Data were expressed as mean±SEM and analyzed by one way ANOVA followed by Bonferroni’s post hoc test where p£0.05 was considered as statistically significant. Results: This study indicate that intrahippocampal colchicine administration significantly impaired spatial memory, and elevated MDA, decreased GPx level in hippocampus of colchicine control rats. In contrast, both pre and post treatment of CE significantly improved spatial memory retention and attenuated the oxidative damage almost to normal. Conclusion:CE is equally effective in prevention as well as alleviation of colchicine induced spatial memory impairment along with hippocampal oxidative stress in male Long-Evans rats. J Bangladesh Soc Physiol 2024;19(1): 9-22